P169 Comparison of Work of Breathing: Heart failure versus Interstitial Lung Disease. (7th October 2021) - Yu, C; Heng, A; Cuesta, R; Roebuck, T; Prasad, J; Naughton, M
Abstract: Background: Heart failure with central sleep apnoea and Cheyne Stokes respiration (HF-CSA-CSR) and interstitial lung disease (ILD) are characterised by tachypnoea, reflecting an increased work of breathing (WOB). Whilst tachypnoea is continuous in ILD, it is periodic in HF-CSA-CSF. Our hypothesis is that the periodicity reflects adaptive efficiency. Methods: We assessed polysomnograms of male patients attending for either heart transplant or ILD assessment. WOB during non-REM sleep was estimated by the breath to breath interval (BBI), from which respiratory rate (RR) was calculated. An age matched control group with snoring, AHI<5 and neither HF or ILD was included. Progress to date: Four patients (mean age 70 years) were identified in each group. The HF-CSA-CSR and ILD groups had similar awake PaCO2. The HF-CSA-CSR group had a lower LVEF and higher TLCO than the ILD group. There was similar BBI in the HF-CSA-CSR group during hyperpneic phase mean = 3.4±0.1 seconds and ILD group mean = 3.5±0.3 seconds, p=0.31. However, the RR during slow wave sleep was significantly lower in the HF-CSA-CSR group compared with ILD and control groups: HF-CSA-CSR mean = 10.3±0.8 breaths/min, control mean = 14.3±1.0 breaths/min, ILD mean 18.2±2.3 breaths/min, P=0.0002. Intended outcome and Impact: This data would suggest that both HF-CSA-CSR and ILD have similar severities of tachypnoea (aka work of breathing) compared with controls, however the RR is significantly lower in the HF-CSA-CSR group compared with ILD, despite similar PaCO2. This would indicate HF-CSA-CSR has similar WOB, yet greater efficiency, than ILD during non-REM sleep.